Diseño de una extensión universitaria con implementación de arquitectura vernácula en el cantón San Lorenzo Esmeraldas - Salazar Midero, Betsy Judiheth (2023)
San Lorenzo is one of the main and largest cantons of Esmeraldas, but it lacks areas or zones for third level educational development. Therefore, we seek to develop a proposal that prioritizes its climatic conditions and generates a proposal in accordance with its environment and population, which is why several important indicators are taken into account, such as proximity to facilities, green areas, mobility and accessibility, to determine in which sector or zone it should be implemented in the architectural project. The objective of this study is to develop an architectural proposal, based on a qualitative and quantitative analysis, to take into account the needs of the sector and its population, providing sustainable solutions, which is reduced in the design proposal of a university extension with implementation of vernacular architecture in the canton San Lorenzo, to reach this proposal a site analysis was conducted to identify the problems of the site, then the process of design and allocation of environments through zoning was carried out, diagrams of relationship, sketches of concepts looking for an optimal functioning of the building, thus complying with the criteria of designs of educational buildings, thanks to this photorealistic images were obtained in SketchUp with V-Ray of facades, plants and perspectives, using criteria of vernacular designs in its facade and interior design, having as protagonist the Chanul wood which is native to the canton, to have a vernacular facade in the form of a marimba.